Left ventricular remodeling in normotensive Wistar rats exposed to intermittent hypoxia of different duration - Yu. M. Kolesnyk; M. Yu. Kolesnyk; O. V. Hancheva; M. I. Isachenko (Zaporozhye State Medical University, 2023)
Intermittent hypoxia has been studied for many years as a promising non-pharmacological method of cardiovascular disease prevention. Hypoxic effects are accompanied by structural and functional changes in the myocardium. There is a direct link between the duration of hypoxic exposures and the severity of left ventricular myocardial remodeling. A range of histochemical markers of myocardial remodeling (cardiotrophin-1, titin, collagen type 1, annexin V) characterizing parenchymal-stromal relationships in the myocardium has shown high informativeness and prognostic value. The aim of the study was to examine cardiotrophin-1, titin, collagen type 1, annexin V and the morphofunctional state of the left ventricle of the heart in experimental rats exposed to intermittent 15-day (IH15) and 60-day hypoxia (IH60). Materials and methods. Intermittent hypoxia was modeled using 30 normotensive male Wistar rats, 7-8 months old, which were randomly assigned to 3 experimental groups of 10 animals each: 1) INT - a control group - intact animals (196.3 ± 6.8 g); 2) IH15 - 15-day hypoxia (205.6 ± 4.1 g); 3) IH60 - 60-day hypoxia (201.1 ± 5.5 g). The study compared the effects of intermittent hypoxia of varying duration: 15-day and 60-day hypoxia. Experimental modeling of intermittent hypoxia of 2 terms revealed a number of differences between the effects dependent on this factor duration through functional (blood pressure measurement, echocardiography) and immunofluorescent studies. Results. Blood pressure in rats of both groups was in the normotensive range, but an increase in systolic by 10 % and diastolic by 19 % was found in IH60 group compared to IH15 group (p < 0.05). In IH15 group, there was a significant decrease in end-diastolic dimension by 20 %, end-systolic dimension by 22 %, an increase in the thickness of left ventricular posterior wall by 44 % and interventricular septum by 33 % as well as left ventricular mass by 12 %, indicating concentric remodeling of the left ventricle, the development of which was confirmed by a 76 % increase in relative wall thickness compared to that in the control group (p < 0.05). Along with these changes, a decrease in end-diastolic volume by 47 %, end-systolic volume by 48 %, stroke volume by 49 % and cardiac output by 50 % with preserved ejection fraction was revealed (p < 0.05). While the parameters of IH60 rats were characterized by an increase in the thickness of interventricular septum by 33 % and left ventricular posterior wall by 17 %, as well as left ventricle mass by 23 %, relative left ventricular wall thickness was 15 % higher than the control value (p < 0.05). At the same time, diastolic volume was 9 % decreased and systolic volume was 24 % increased (p < 0.05). Also, cardiac output was increased by 58 % compared to that in 15-day hypoxic rats with an 8 % decrease in ejection fraction (p < 0.05). The concentrations of markers in IH60 group exceeded those in IH15, namely: cardiotrophin-1 by 39 %, titin by 70 %, collagen type 1 by 60 % and annexin V by 130 % (p < 0.05). Conclusions. 15-day hypoxia forms concentric left ventricular hypertrophy according to echocardiography findings; the study of marker profile of myocardial remodeling has revealed the development of moderate hypertrophy with increased resilient-elastic properties and decreased intensity of cardiomyocyte death. Remodeling caused by 60-day hypoxia is characterized by the eccentric pattern of changes with severe hypertrophy, significant fibrosis associated with apoptosis of cardiomyocytes. Such morphofunctional state of the myocardium may indicate the initial stages of maladaptation, increasing the risk of heart failure development.